1999
DOI: 10.1038/sj.onc.1203044
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytic differentiation of myeloid progenitor cells by p130, the retinoblastoma tumor suppressor homologue

Abstract: The retinoblastoma protein (pRB) and the related pocket proteins, p107 and p130, play crucial roles in mammalian cell cycle control. Recent studies indicate that these pocket proteins are also involved in cellular di erentiation processes. We demonstrate in this work that the pRB-related p130 selectively accumulates during the in vitro di erentiation of the myeloid progenitor cell, 32Dcl3, into granulocyte in response to granulocytecolony stimulating factor (G-CSF). This G-CSF-dependent granulocytic di erentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…This ®nding supports redundancy of cdki's for the p21 role in di erentiation. Indeed, p19 (Adachi et al, 1997), p27 (Matsumura et al, 1997) and Rb-family member p130 (shown to be capable of substituting for cdki's in knockout mice (Coats et al, 1999;Mori et al, 1999)) can initiate myeloid or megakaryocytic di erentiation upon transfection into cell lines.…”
Section: Involvement Of P21 In Differentiationmentioning
confidence: 99%
“…This ®nding supports redundancy of cdki's for the p21 role in di erentiation. Indeed, p19 (Adachi et al, 1997), p27 (Matsumura et al, 1997) and Rb-family member p130 (shown to be capable of substituting for cdki's in knockout mice (Coats et al, 1999;Mori et al, 1999)) can initiate myeloid or megakaryocytic di erentiation upon transfection into cell lines.…”
Section: Involvement Of P21 In Differentiationmentioning
confidence: 99%
“…Cells were cultured in RPMI 1640 medium containing 10% fetal calf serum and 20% WEHI-3B-conditioned medium (20% WEHI) as a source of interleukin 3 (IL-3). Stable transfectants that conditionally express p107HA, p107⌬S/T-P-HA, or E1A were created by transfecting pOPTET-BSD-p107HA, pOPTET-BSD-p107⌬S/ T-P-HA, or pOPTET-BSD-E1A into 6-1 cells by electroporation as described (34,38). Expression of the cDNA-directed proteins in these transfectants was repressed in medium containing 1 g/ml tetracycline (Tc) and was induced in medium containing 5 mM isopropyl ␤-D-thiogalactopyranoside (IPTG) for 24 h in the absence of Tc.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that growth of hematopoietic cells such as BaF3 and 32D is strongly inhibited by ectopic expression of p130, but not by pRB, even in its phosphorylationresistant form (34,38). In these cells, p130 prevents S phase entry, at least in part, through inhibiting the transcriptional activity of E2F-4 (34).…”
Section: P107-mediated S Phase Cell Cycle Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…These substrates might be one or more positive regulators of granulocytic differentiation 45,46 and/or negative regulators of proliferation during granulocytic differentiation, including the p130 pocket protein, p27, STAT-3, and C/EBP␣. [47][48][49][50][51][52][53] To begin to test this hypothesis, we measured the expression of p130 before and after CUL-4A-HA2 and control cells were induced to differentiate into granulocytes. The expression of c-myc, whose expression must be downregulated for the differentiation of myeloid cell lineages, including granulocytes, was also measured in these cells.…”
mentioning
confidence: 99%